Ernesta Farnika uwagi o przedstawieniach Teatru Polskiego w Katowicach (PDF 3,03 MB) (Książnica Śląska, 2025)
Ernest Farnik was a theatre lover, for years, he cooperated with theSociety of Friends of the Polish Theatre in Katowice, served on several committees assessing plays for people’s theatres, was a viewerof numerous performances, as well as the owner of a large collectionof theatrical items. The author of the article analyses the reviews of Ernest Farnik from the theatre season 1933/1934, recorded on copiesof theatre programme brochures from his legacy and compares themwith theatrical reviews published in the press (“Polska Zachodnia”,“Polonia”, “Górnoślązak”, “Goniec Śląski”). Simultaneously, she delvesinto the state of the theatrical scene at that time, describes the alterations taking place within the theatre, and recalls individuals associated with the then theatre and artistic life in Upper Silesia.